Parathyroid hormone as early marker of derangements of mineral metabolism among patients in various stages of chronic kidney disease - M. Rasheed Khan; A.G. Thivyahprabha; K. Durga Sowmithri; M. Ganesha Pandian (Al Ameen Medical College, 2023)
Background: Chronic Kidney Disease (CKD) is an international public health problem affecting about 5-10% of the population. As kidney function declines, there is a progressive deterioration in mineral homeostasis with disruption of normal serum concentrations of phosphorus, calcium and changes in circulating levels of parathyroid hormone (PTH). Objectives: To correlate serum intact parathyroid hormone, urea, creatinine, calcium, phosphorus and alkaline phosphatase in various stages of CKD and to compare the same with the control group. To find the role of intact parathyroid hormone in the early diagnosis of mineral disturbances in CKD patients. Methodology: This study was carried out for a period of six months on confirmed cases of CKD visiting Nephrology OPD. Patients in various stages of CKD were included in the study. After informed consent blood samples were collected. Results: The mean level of PTH in cases is 136.80 ±92.70 where as in controls mean PTH level is 52.47 ±16.34 pg/mL. Statistically significant increase in levels of PTH were seen in patients than controls (P<0.001). Conclusion: A statistically significant increase in PTH levels from stage III of CKD was observed when calcium and phosphorus were still within reference range. Thus PTH levels can be used as a marker to identify the mineral disturbances in early stages of CKD.